2013
DOI: 10.1002/14651858.cd008813.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Manual small incision cataract surgery (MSICS) with posterior chamber intraocular lens versus phacoemulsification with posterior chamber intraocular lens for age-related cataract

Abstract: Manual small incision cataract surgery (MSICS) with posterior chamber intraocular lens versus phacoemulsification with posterior chamber intraocular lens for age-related cataract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
53
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 27 publications
3
53
1
1
Order By: Relevance
“…9 Trials were conducted in India, Nepal and South Africa. Follow up ranged from one day to six months, but most trials reported at six to eight weeks after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…9 Trials were conducted in India, Nepal and South Africa. Follow up ranged from one day to six months, but most trials reported at six to eight weeks after surgery.…”
Section: Resultsmentioning
confidence: 99%
“…A recent Cochrane review (2012) found more patients achieved unaided vision of ≥6/12 following SICS than extracapsular cataract extraction, traditionally the surgical approach used in low‐resource countries . Furthermore, some studies suggest SICS may actually achieve similar best corrected vision to phacoemulsification, with the advantage of SICS being considerably cheaper …”
Section: Introductionmentioning
confidence: 99%
“…6 Furthermore, some studies suggest SICS may actually achieve similar best corrected vision to phacoemulsification, with the advantage of SICS being considerably cheaper. 4,7,8 Although the provision of eye care services in the developing world is critical, providers of such care must ensure these services meet best clinical care and the quality standards as specified by the World Health Organisation. 9 Unfortunately, the analysis of surgical outcomes following cataract surgery in low resources settings have been limited by retrospective data collection methods, incomplete clinical documentation and poor patient attendance at follow-up visits.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 However, a recent meta-analysis showed that phacoemulsification was more likely than SICS to give an uncorrected visual acuity of 6/18 or better soon after surgery. 11 The equipment required for phacoemulsification is expensive and this technique has not been widely adopted in lower-income settings. However, ophthalmologists in LMICs are buying phacoemulsification machines to provide this service to wealthier patients paying high fees.…”
Section: Introductionmentioning
confidence: 99%